2019
DOI: 10.1016/j.ces.2019.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Linking power and flow in rotor-stator mixers

Abstract: The relationship between power and flow characteristics of batch rotor-stator mixers has been studied using CFD simulations with experimental power validation. The mixer studied was the Silverson L5M batch mixer with the standard emulsor head. The size of the holes in the screen and the constriction of the base hole were changed in small increments. The MRF technique was used to model rotor rotation. A model is developed in this study which links the power and flow numbers of the mixer. Since power is easy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…This relationship, being linear and with a non‐zero intercept, has not been incorporated into any other predictions of the power number in stirred vessels. The same relationship has been found for both in‐line 23–25 and batch 26,27 rotor‐stator mixers operating in the fully turbulent regime. Interestingly it was found that when changing between batch and in‐line mode in a rotor‐stator mixer, not only is the relationship between the flow number and the power number the same form, but the empirical constants are also the same.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…This relationship, being linear and with a non‐zero intercept, has not been incorporated into any other predictions of the power number in stirred vessels. The same relationship has been found for both in‐line 23–25 and batch 26,27 rotor‐stator mixers operating in the fully turbulent regime. Interestingly it was found that when changing between batch and in‐line mode in a rotor‐stator mixer, not only is the relationship between the flow number and the power number the same form, but the empirical constants are also the same.…”
Section: Introductionsupporting
confidence: 75%
“…The full equation for predicting power number in rotor‐stator mixers is given by Po=kRe+k1NQ+PoZ, where k , k 1 , and Po Z are empirical constants to be obtained from experimental data which depend on the mixer geometry 27 . Of course, in the laminar regime where Re is small, the first term on the right hand side of Equation () dominates and the remaining terms are negligible.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of revealing the effects of the operating parameters and structural parameters on the emulsification performance, the flow field is numerically studied using ANSYS Fluent. The multiple reference frames (MRF) model is adapted when solving the momentum equations for the entire domain; that is, a rotating frame is used for the region containing the rotor while a stationary frame is used for other regions of the domain, as shown in Figure . Grids are generated in ANSYS Meshing to achieve the discretization of the computational domain and are further refined based on the velocity gradient .…”
Section: Methodsmentioning
confidence: 99%
“…The power consumption was calculated by the torque on the rotor in this work, which is shown in eq . , CFD simulation method is widely applied to evaluate the torque on the rotor in HSMs. John et al validated the CFD simulation method to predict the power consumption by experimental measurements in both inline and batch HSMs. where N denotes the rotor speed and M represents the torque on the rotor.…”
Section: Experimental Methodsmentioning
confidence: 99%